2018
DOI: 10.1002/14651858.cd005290.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and acupressure for premenstrual syndrome

Abstract: BackgroundAcupuncture has a history of traditional use in China for women's health conditions including premenstrual syndrome (PMS), but its e ectiveness for this condition remains unclear. This review examined the available evidence supporting the use of acupuncture or acupressure to treat PMS. ObjectivesTo evaluate the e ectiveness and safety of acupuncture or acupressure for women with PMS or premenstrual dysphoric disorder (PMDD). Search methodsWe searched the Cochrane Gynaecology and Fertility Specialised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 35 publications
0
54
0
6
Order By: Relevance
“…epilepsy). Other psychologic and behavioural PMS symptoms include: sugar and salt cravings, tension or anxiety, irritability, crying and tearfulness, fatigue, depressed mood, insomnia or hypersomnia, forgetfulness or confusion, panic attacks, aggression and depression [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…epilepsy). Other psychologic and behavioural PMS symptoms include: sugar and salt cravings, tension or anxiety, irritability, crying and tearfulness, fatigue, depressed mood, insomnia or hypersomnia, forgetfulness or confusion, panic attacks, aggression and depression [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has been effective at reducing tension headaches/migraines, Parkinson's disease symptoms, fibromyalgia, chronic neck and back pain, osteoarthritis pain and ineffective at reducing symptoms of carpel tunnel, abdominal pain due to surgery and consistent, long-term general pain reduction (Murray, 1995;Chou et al, 2008;Reinhold et al, 2008;Plank and Goodard, 2009;Cho et al, 2012). Regarding psychopathology, acupuncture has demonstrated promising results for alleviating depression, bipolar disorder and mood associated with premenstrual disorder (Zhong et al, 2008;Dennehy et al, 2009;Zhang et al, 2010;Armour et al, 2018). Two meta-analyses demonstrated that acupuncture effectively treats major depressive disorder (MDD) and post-stroke depression (PSD) and should be considered an alternative treatment to antidepressants.…”
Section: Functional Relaxation Therapy: Non-tactile Self-administeredmentioning
confidence: 99%
“…The included CSRs focused on 50 different diseases or conditions. Eight reviews (16%) evaluated acupuncture for joint and muscle pain [8,18,20,22,23,25,34,36], 5 reviews (9%) for obstetrics [11,16,41,42,44], 5 reviews (9%) for gynecological diseases [7,31,32,43,56], 3 reviews (4%) for stroke [51,52,54] and 2 reviews (4%) for smoking cessation [21,48] The other diseases are listed in Table S1.…”
Section: Treated Conditionsmentioning
confidence: 99%